Speciation of chromium compounds from humic acid-zeolite Y to an ionic liquid during extraction. (March 2018) - Huang, Hsin-Liang; Wei, Yu Jhe
Abstract : By synchrotron X-ray absorption spectroscopy, chemical structures of hexavalent chromium (Cr(VI))/trivalent chromium (Cr(III)) adsorbed on humic acid (HA)-zeolite Y and extracted in an ionic liquid (1-butyl-3-methylimidazolium tetrafluoroborate ([C4 mim][BF4 ])) have been studied. By combining the competitive adsorption results and reduction of Cr(VI)-HA with the carboxyl groups of HA, Cr(III)-HA (58%) was shown to be the major compound in HA-zeolite Y using synchrotron X-ray absorption near-edge structure (XANES) spectroscopy. In an ionic liquid phase, the reduction of Cr(VI)-HA to Cr(III)-HA and the desorption of Cr(III) from HA were caused by [C4 mim][BF4 ]. The 9 F nuclear magnetic resonance (NMR) spectra show that the perturbation of the [C4 mim][BF4 ] anion was affected by the extractable chromium species. The formation of a Cr(III) ion affected the increase in the bond distance for the 1st shell CrO of the chromium species in [C4 mim][BF4 ] using extended X-ray absorption fine structure (EXAFS) spectroscopy. The changes in the non-extractable chromium species remaining in HA-zeolite Y were also caused by [C4 mim][BF4 ] during extraction. The desorption of the absorbed Cr(III) on HA and zeolite Y was observed to form Cr(III) ions. As the percentage of Cr(III) ions remaining in HA-zeolite Y increased, a slightly greater bond distance for CrO was found at 2.01 Å. The enhanced reduction of Cr(VI)-HA and desorption of Cr(III) adsorbed on the HA and zeolite Y to form Cr(III) ions were affected by [C4 mim][BF4 ]. Increased mobility of Cr(III) in the simulated soil can promote the migration of Cr(III) ions into the H2 O during soil washing for remediation. Graphical abstract: Highlights: The reduction and desorption of Cr compounds in an ionic liquid (IL) increased the mobility of Cr(III) in simulated soil for remediation. Interaction between IL anions and Cr compounds occurred in IL. The remediation of contaminated soils is revealed in molecular-scale understandings.